Can PRGF Policy Levers Improve Institutions and Lead to Sustained Growth?. (Policy Papers; Policy Paper, 2005)
Broad economic institutions are of fundamental importance for sustained economic growth. Changing these institutions is difficult, particularly for outsiders. But this does not mean that there is no role for the Fund to play in assisting low-income countries to create conditions for sustained growth acceleration.